PROPOSTA DE UM MODELO DE SISTEMA DE GESTÃO INTEGRADA DE MEIO AMBIENTE E SEGURANÇA INDUSTRIAL PARA EMPREENDIMENTOS DE CONSTRUÇÃO E MONTAGEM DE COMPONENTES MODULADOS PARA PLATAFORMAS OFF-SHORE DE PETRÓLEO - Gomes, Cristiano Keil (2008)
The present dissertation presents a proposal of an Integrated Environmental and Industrial Safety Management Systems for construction and assembly undertakings of modulated components oil off-shore platforms. The work is done through a case study for construction and assembly on the Petrobras platforms P-51, P-52, P-53. It suggests a management system with requirements in agreement with the standards ISO 14001:2004, OHSAS 18001:1999 and specific requirements of environment, safety and occupational health. Moreover, the study approaches environment, safety and occupational health current aspects in this kind of undertakings and the requirements for a management system which is suitable with a construction and assembly scenario.